Analisis Aliran Daya Sistem Tenaga Listrik Pada PT. Sele Raya Merangin Dua Menggunakan Metode Newton-Raphson - Doan Yudanto; Dasrinal Tessal (Journal of Electrical Power Control and Automation (JEPCA), 2021)
Power flow analysis is used to determine the power flow parameters that are useful for planning the system to operate optimally as well as changes to existing systems, such as what happened at PT. Sele Raya Merangin Dua, which is currently making system changes in the form of additional loads. With the addition of this load, it is necessary to conduct a power flow analysis to determine the effect of increasing the load with the aim of knowing the system performance so that it can be in optimal condition. The research method used is qualitative-descriptive which is carried out in a simulation using ETAP 12.6 software where the results of the simulation will be tabulated and graphed. The results showed that the increase in load caused an increase in power generation and power distribution, especially on swing-buses to load-buses and branch buses. From the previous generation power of 1069.1 kVA increased to 1155.2 kVA but did not affect the performance of each power system equipment PT. SRMD and the electric power system are still in optimal condition.